Chromogranin A‐positive hormone‐negative endocrine cells in pancreas in human pregnancy. Issue 2 (6th January 2021) - Moin, Abu Saleh Md; Zeng, Kylie; Rizza, Robert A.; Dhawan, Sangeeta; Butler, Alexandra E.
Abstract: Introduction: We sought to determine whether chromogranin A‐positive hormone‐negative (CPHN) endocrine cells are increased in the pancreas of pregnant women, offering potential evidence in support of neogenesis. Methods: Autopsy pancreata from pregnant women ( n = 14) and age‐matched non‐pregnant control women ( n = 9) were obtained. Staining of pancreatic sections for chromogranin A, insulin and a cocktail of glucagon, somatostatin, pancreatic polypeptide and ghrelin was undertaken, with subsequent evaluation for CPHN cell frequency. Results: The frequency of clustered β‐cells was increased in pregnant compared to non‐pregnant subjects (46.6 ± 5.0 vs. 31.8 ± 5.0% clustered β‐cells of total clustered endocrine cells, pregnant vs. non‐pregnant, p < .05). Frequency of endocrine cocktail cells was lower in pregnant women than non‐pregnant women (36.2 ± 4.0 vs. 57.0 ± 6.8% clustered endocrine cocktail cells of total clustered endocrine cells, pregnant vs. non‐pregnant, p < .01). No difference in frequency of CPHN cells was found in islets, nor in clustered or single cells scattered throughout the exocrine pancreas, between pregnant and non‐pregnant women. The frequency of CPHN cells in pregnancy was independent of the number of pregnancies (gravidity). Conclusions: Our findings of no increase in CPHN cell frequency in pancreas of pregnant women suggest that this potential β‐cell regenerative mechanism is not that by which the increased β‐cell mass of pregnancy is achieved. However, an increase in the percentage of clustered β‐cells was found in pregnancy, with decreased frequency of other endocrine cells in clusters, suggesting a compensatory shift from other pancreatic endocrine cell types to β‐cells as a mechanism to meet the increased insulin demands of pregnancy. Abstract : Chromogranin A‐positive hormone‐negative (CPHN) endocrine cells are increased in the pancreas of pregnant women, offering potential evidence in support of neogenesis; we found no increase in CPHN cell frequency in pancreas of pregnant women suggesting that this potential β‐cell regenerative mechanism is not that by which the increased β‐cell mass of pregnancy is achieved. However, an increase in the percentage of clustered β‐cells was found in pregnancy, with decreased frequency of other endocrine cells in clusters, suggesting a compensatory shift from other pancreatic endocrine cell types to β‐cells as a mechanism to meet the increased insulin demands of pregnancy.